Work engagement, job satisfaction and turnover intention among nurses working in private hospitals of Pokhara, Nepal - Sujata Kandel; Hari Prasad Kaphle (PLoS ONE, 2026)
Background Understanding nurses’ engagement and drivers is crucial as it impacts patient experience, safety and healthcare quality. Despite the rapid growth of the private healthcare sector and numbers of nurses, little is known about the factors influencing work engagement and its relationship with job satisfaction and turnover intention among nurses in private hospitals of Nepal, where working conditions and organizational structures differ from the public sector. This study aims to assess work engagement levels, identify factors that increase or decrease work engagement among nurses, and determine its association with job satisfaction and turnover intention. Methods A facility-based cross-sectional study among 211 nurses in private hospitals of Pokhara was conducted from September to October, 2024 using a self-administered structured questionnaire. The questionnaire assessed work engagement as the dependent variable and job satisfaction and turnover intention as outcome variables. Work engagement was measured using the 17-item Utrecht Work Engagement Scale, while job satisfaction and turnover intention were measured using the 5-item Short Index of Job Satisfaction and the 3-item Turnover Intention Scale, respectively. Multistage random sampling was applied, and data were entered in Epi Data and analyzed in SPSS. Descriptive statistics and inferential analyses, including Chi-square tests was used to identify the associated factors and logistic regression was used to measure the strength of association between opportunities for career development and perceived workload with work engagement. Results The mean score for work engagement among nurses working in private hospitals is 4.29 ± 0.72, which is considered to be high. Binary logistic regression showed that opportunities for career development (aOR: 9.256, 95% CI: 1.803–47.511) and perceived workload (aOR: 3.586, 95% CI: 1.170–10.989) were found to be associated with work engagement. Similarly, there found a significant association between work engagement and job satisfaction (aOR: 5.076, 95% CI: 2.557–10.076). Conclusion Nearly two third of the nurses working in private hospitals had high work engagement level. In multi-variates logistic regression analysis, opportunities for career development and perceived workload were found to be associated with work engagement. Work engagement was found to be significantly and positively associated with job satisfaction.